Soliton transmission through disordered system - Kovalev, A.S.; Prilepsky, J.E.; Gredeskul, S.A.; Derevyanko, S.A. (Физика низких температур, 2008)
An exact formula for the transmission time in the disordered nonlinear soliton-bearing classical one-dimensional
system is obtained.